Interfacial structure and boundary lubrication of a dicationic ionic liquid - Perez-Martinez, C; Perkin, S (American Chemical Society, 2019)
We report measurements of the normal surface forces and friction forces between two mica surfaces separated by a nanofilm of dicationic ionic liquid using a Surface Force Balance. The dicationic ionic liquid 1,10-bis(3-methylimidazolium)decane di[bis(trifluoromethylsulfonyl)imide] forms a layered structure in nanoconfinement, revealed by oscillatory structural forces. Friction measurements performed at different film thicknesses display quantized friction, i.e., discontinuities in friction as layers are squeezed out and friction coefficients dependent on the number of liquid layers confined between the surfaces. The details of the friction traces indicate a liquidlike film, and, surprisingly, decreasing friction with increasing water content; we discuss possible mechanisms underlying these observations. This latter trait may be helpful in applications where ionic liquid lubricants cannot be insulated against humid environments.